Heart Rate and Perceived Experience Differ Markedly for Children in Same- versus Mixed-Gender Soccer Played as Small- and Large-Sided Games. (5th August 2018) - Póvoas, S.; Randers, M. B.; Krustrup, P.; Larsen, M. N.; Pereira, R.; Castagna, C.
Abstract : This study examines heart rate (HR) and perceived experience during same- versus mixed-gender soccer played as small- (SSG) and large-sided (LSG) games. HR, rating of perceived exertion (RPE), and fun scores were determined in 134 pupils (50 girls, 84 boys) randomly assigned to same- and mixed-genders formats playing 2x15-min of SSG (2v2, 4v4) and LSG (12v12) in a random order (~50 m 2 /player). HR was lower ( p ≤0.03) for girls when playing together with boys than when playing alone (71±10 versus 77±7%HRmax), while being similar for boys playing mixed- or same-gender games (74±7 versus 77±4%HRmax). Boys perceived less fun when playing together with girls than when playing alone (4.4±2.3 versus 6.3±2.3, p <0.001). Irrespective of gender, higher ( p <0.001) HRmean, %time>80%HRmax, and RPE were observed during 2v2 (78±9%HRmax, 43±33%, 5.5±2.5) and 4v4 (76±9%HRmax, 39±32%, 5.5±2.7) than during 12v12 (70±10%HRmax, 23±27%, 3.8±2.9). Cardiovascular strain was lower for girls when playing together with boys than when playing alone in LSG. SSG were more intense than LSG when girls played mixed-gender games and when boys played mixed- and same-gender games. When boys played mixed-gender games, SSG were considered more fun than LSG. Physical education teachers and coaches should consider gender and game format differences when using soccer.